Production of Chrysanthemum in plugs is remunerative - Kumar, Gunjeet; Vanlalruati, Vanlalruati; Anand, Prativa; Sindhu, S S (Indian Horticulture, 2019)
Chrysanthemum is grown in open as well as protected environments for cut and loose flowers and pot mums. It is a facultative short-day plant for flower bud initiation and obligate short-day plant for flower bud development. Minimum continuous dark period per day, necessary for flower bud initiation, is not lesser than 9.5 hours per day. Photoperiod required for bud development is one hour shorter than that required for bud initiation. In India, chrysanthemum is grown in 16,630 ha with a total production of 1,79,370 tonnes of loose flower and 5,720 tonnes of cut flower.